Barriers of dental care utilization for children living in military and civilian areas - Amrita Sujlana; Devinder Baweja; Avninder Kaur; Pannu Parampreet Kaur (Wolters Kluwer Medknow Publications, 2016)
Aim: We planned our study to assess whether easy access to dental care facilities result in improved oral health and increased utilization of dental services by children. Materials and Methods: Four hundred child-parent pairs, 200 each from the military and civilian areas, were randomly selected (children aged 5 years). Prior to the clinical examination of their wards, parents were asked to complete a questionnaire regarding their sociodemographic details, family structure, dental care utilization, and attitudinal variables toward oral health. Dental caries prevalence and treatment needs were assessed using the World Health Organization (WHO) criteria (1997). Statistical Analysis Used: Students' t-test and chi-square test were used to assess the significance of difference between the two groups. Multivariate regression analysis was performed for all covariates associated with the child's dental attendance pattern. Results: The percentage prevalence of children affected by dental caries was observed to be statistically higher in the civilian area. The mean decayed, missing, and filled teeth (DMFT) score was 2.35 ± 2.92 and 3.26 ± 3.35 in the military and civilian areas, respectively (t stat = 2.78, P = 0.002). The percentage of teeth requiring treatment was observed to be 22.5% and 27.6% in the military and civilian areas, respectively (χ2 = 16.77, P < 0.0001). Covariates significantly associated with increased child's dental attendance were identified as: High level of the mother's education, regularity of dental visits by the parents, the child's increased brushing frequency, and past caries experience. Conclusion: Despite the adequate availability of dental facilities in military areas, untreated dental problems are prevalent. Our finding confirms that dental care utilization is not solely access-related, and other barriers need to be investigated.